Intraoperative pediatrics hypothermia and its factors during general anesthesia at comprehensive specialized hospitals, Northwest Ethiopia: Multicenter follow up study - Melese Tadele Mekonnen; Salh Yalew Mustofa; Yophtahe Weldegerima Berhe; Nurhusen Riskey Arefayne; Biresaw Ayen Tegegne (PLoS ONE, 2025)
Background The human body can regulate its internal temperature under physiological conditions by balancing heat production and loss. Many pediatric patients may experience hypothermia during surgery and anesthesia. Hypothermia is defined as a core body temperature below 36 °C in pediatric patients undergoing surgery. Therefore, this study was aimed to determine the incidence of intraoperative pediatric hypothermia and its factors during general anesthesia at Comprehensive Specialized Hospitals, Northwest Ethiopia. Methods A multi-center prospective follow-up study was conducted from May 2 to July 28, 2023, on 403 participants. A consecutive sampling method was used to select the study participants. Preoperative temperature and initial intraoperative temperature were measured using tympanic thermometer. Descriptive data was carried out and the results were presented as table, text and graph. Data was entered to Epi-data software (version 4.6) and analyzed with STATA software (version 17 SE). Bivariable and multivariable logistic regression analyses were used to identify associated factors. A p-value less than 0.05 with a 95% confidence interval were considered statistically significant. Result The incidence of intraoperative pediatric hypothermia was 44.7% (CI=39.8–49.6). The neonates (AOR=3.7,95%CI=1.5–10.8), use of intravenous fluid>500ml (AOR=2.3,95%=1.48–4.43), having blood transfusion (AOR=2.7,95% CI=1.30–5.91), operation room temperature ≤21 degree Celsius (AOR=9.3, 95% CI= 5.78–20.58), operation room temperature in between 22–240c (AOR=2.6, 95%CI=1.28–5.35) and preoperative core temperature≤ 35.9 degree Celsius (AOR=4.8,95%CI=2.42–9.68) were associated with intraoperative pediatric hypothermia during general anesthesia. Conclusion and recommendation This study showed that the incidence of intraoperative hypothermia among pediatric surgical patients was considerably high. Neonate, using more than 500ml of intravenous fluid, having blood transfusion, preoperative core temprature≤35.9 °C and operation room temperature ≤21 °C were associated with intraoperative hypothermia during general anesthesia. Pediatric patients should be monitored their core body temperature during the intraoperative period to prevent and treat hypothermia. Emphasis should be given for neonates. Warming the operating room is recommended. We also recommend to use the optimal fluid and blood transfusion.